2021
DOI: 10.1039/d1cy00278c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a ZnIn2S4–ZnAlOx nanocomposite for photoreduction of CO2 to CO

Abstract: Solar-driven CO2 conversion into fuels and sustainable energy has attracted increasing attention around the world. However, the efficiency of the transformation remians relatively low due to the rapid recombination of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The peak at 533.9 eV agreed with the surface oxygen chemisorbed. ,, The peak of In–O bonds was stronger than that of Zn–O bonds in ZIO, indicating that the content of In was more and the phase of In­(OH) 3 was mainly formed, which was consistent with the results of XRD. Sulfurization induced a negative shift of the Zn 2p and In 3d peaks. , …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The peak at 533.9 eV agreed with the surface oxygen chemisorbed. ,, The peak of In–O bonds was stronger than that of Zn–O bonds in ZIO, indicating that the content of In was more and the phase of In­(OH) 3 was mainly formed, which was consistent with the results of XRD. Sulfurization induced a negative shift of the Zn 2p and In 3d peaks. , …”
Section: Resultsmentioning
confidence: 95%
“…Sulfurization induced a negative shift of the Zn 2p and In 3d peaks. 41,42 Optical and Photoelectronic Characterization. The photocatalytic properties of semiconductors mainly depend on their light adsorption properties, which in turn are related to their electronic structures.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…After the photocatalytic CO 2 reduction reaction, three transmittance peaks of intermediate products are detected on the sample Cu(2)–SnO 2 , including adsorbed/activated CO 2 * (1200–1300 cm −1 ), formate *COOH (1400–1500 cm −1 ), and bidentate bicarbonate b-HCO 3 − (1600–1650 cm −1 ). 23,35,36 The obvious transmittance peaks suggest that the adsorbed sample Cu(2)–SnO 2 can be effectively activated, and the appearance of the *COOH peak suggests that CO 2 reduction follows a *COOH pathway, which also explains the reason of the high selectivity of CO.…”
Section: Resultsmentioning
confidence: 99%
“…can regulate the electronic structure of a catalyst, which not only greatly enhances the chemisorption ability of CO 2 and the binding intensity of the reaction intermediates, but also promotes the separation of photogenerated electron-hole pairs, improving the catalytic activity and product selectivity. 15,[22][23][24][25][26] For example, Liu et al constructed a flower-like SnS 2 /SnO 2 junction, which greatly promotes the effective separation and transfer of photogenerated charges, harvesting an excellent CO 2 conversion efficiency. 15 Xu et al reported isolated single-atom cobalt in the ZnIn 2 S 4 monolayer with dual active centers of Co and Zn, which can facilitate the activation of CO 2 .…”
mentioning
confidence: 99%
“…ZnIn 2 S 4 (ZIS) was prepared by the solvothermal method. [60] Typically, 115.0 mg of ZnSO 4 • 7H 2 O, 234.5 mg of InCl 3 • 4H 2 O, and 100 mg of hexadecyl trimethyl ammonium bromide (CTAB) were dissolved in 30 mL of isopropyl alcohol and magnetically stirred for 30 min at room temperature. Then, 185 mg of thioacetamide (TAA) was added to the above solution.…”
Section: Synthesis Of Pristine Znin 2 Smentioning
confidence: 99%